Adenovirus virus-associated RNA and translation control - Mathews, M B; Shenk, T (Journal of virology, 1991)
The adenovirus genome is transcribed by two RNA polymerases furnished by the host cell. RNA polymerase II transcribes both strands of the viral DNA over nearly all of its length, and the resultant mRNAs encode more than 50 viral proteins. RNA polymerase III transcribes less than 1% of the viral genome, giving rise to one or two species (depending on the virus serotype) of short, noncoding RNAs. This RNA was named virus-associated (VA) RNA when its origin from the viral genome was still uncertain. Even though VA RNA was detected in infected cells as early as 1966, its role in translational control and in counteracting host antiviral defenses only became apparent in the 1980s and the details of its action remain the subject of active investigation. VA RNAs are common to all adenoviruses studied to date, but most work has concentrated on the group C adenoviruses, adenovirus types 2 and 5 (Ad2 and Ad5), upon which this review will necessarily focus.